Análisis de la Fan Page en Facebook de Franco Quezada y la influencia de su campaña electoral seccional en las parroquias urbanas Carigán, el Valle y el Sagrario del cantón Loja, período enero febrero 2023 - Ordóñez Cando, María Verónica (2024)
The research study focused on the " ANÁLISIS DE LA FAN PAGE EN FACEBOOK DE FRANCO QUEZADA, Y LA INFLUENCIA DE SU CAMPAÑA ELECTORAL SECCIONAL EN LAS PARROQUIAS URBANAS CARIGÁN, EL VALLE Y EL SAGRARIO DEL CANTÓN LOJA, PERIODO ENERO- FEBRERO 2023," seeking to reveal the impact that this social network had on the aforementioned candidate's political campaign. Facebook has become a relevant tool in electoral campaigns; thanks to this platform, politicians can reach areas that are geographically dispersed. Therefore, in this research, we aim to analyze this social network in the political arena, focusing on how it was managed during the sectional electoral campaign of Franco Quezada in the urban parishes of Loja Canton mentioned above. Considering this, the importance of combining digital and traditional strategies to achieve successful results in local elections will be emphasized. The segmentation and personalization of political messages on Facebook are crucial. When combined with electoral advertising and political content, they can influence voters' attitudes, leading to victory. A mixed methodology was employed, using both quantitative and qualitative techniques applied to the population under study and experts involved in the influence of Facebook. These methods were adapted to the research objectives, focusing on the perception of users aged 30 to 39 regarding the political proposals published on Franco Quezada's Facebook Fan Page. Additionally, the type of content and the frequency of posts on that page will be determined.